Kemandirian dan Kreativitas Belajar serta Pengaruhnya dalam Pemahaman Konsep Matematika - Hawa Liberna; Maya Nurfitriyanti; Sri Agustini (Universitas Indraprasta PGRI Jakarta, 2022)
Understanding mathematical concepts is a basis for students in understanding mathematic lesson. By a good understanding of mathematical concepts, students are able to solve problems, especially mathematic problem. Unfortunately, there are still many students who do not understand the important of understanding mathematical concepts. The purpose of this study is to determine 1) The effect of independence and learning creativity on understanding mathematical concepts simultaneously, 2) The effect of learning independence on understanding mathematical concepts, 3) The influence of learning creativity on understanding of mathematical concepts. The number of samples in this study was as many as 89 students at North Jakarta Junior High School in academic year 2021/2022 with proportional random sampling. Based on the results of the hypothesis, it can be concluded that 1) There was a significant effect of independence and learning creativity on understanding mathematical concepts together. This was evidenced by the Sig value of 0,000 <0,05 and Fcount of 62,542. 2) There was a significant effect of learning independence on the understanding of mathematical concepts. This was evidenced by the Sig value of 0,000 <0,05 and tcount of 4,307. 3) There was a significant effect of learning creativity on understanding mathematical concepts. This was evidenced by the Sig value of 0,000 <0,05 and tcount of 3,837.